2007
DOI: 10.1007/s10340-007-0176-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of aerosol devices for simultaneous disruption of sex pheromone communication in Cydia pomonella and Grapholita molesta (Lepidoptera: Tortricidae)

Abstract: A two-year study was conducted evaluating PuVer ® aerosol dispensers (Suterra LLC, Bend, OR, USA) for mating disruption of codling moth, Cydia pomonella (L.), and the oriental fruit moth, Grapholita molesta (Busck). The PuVer ® dispenser consists of a pressurized metal canister loaded with pheromone active ingredients dissolved in solvent and housed within a circuit-controlled, plastic dispensing cabinet programmed to release an aerosol spray of pheromone at regular intervals. PuVers ® were deployed at the lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 35 publications
1
47
2
3
Order By: Relevance
“…These results are contrary to the trend observed by Suckling et al (2007), who showed that mating disruption does not exceed 90% using diffusers at low density. The reduction of the mating interruption index in the last two years may be related to the Oriental fruit moth population increase of almost 25 fold during those years.…”
Section: -2007contrasting
confidence: 99%
See 4 more Smart Citations
“…These results are contrary to the trend observed by Suckling et al (2007), who showed that mating disruption does not exceed 90% using diffusers at low density. The reduction of the mating interruption index in the last two years may be related to the Oriental fruit moth population increase of almost 25 fold during those years.…”
Section: -2007contrasting
confidence: 99%
“…Biolita ® consists of a polypropylene diffuser (9x12 cm) containing 4.10 g of a 90:6:1 mixture of (Z)-8-dodecenyl acetate (89.93%); (E)- Evaluation of the effectiveness of mating disruption. The efficiency of the mating disruption formulation in confusing the chemical communication between male and female oriental fruit moths was calculated by the mating interruption index (MII), MII = (M-P/P)*100, where M is the average number of males captured per trap in mating disruption plots and P is the number of captures in the conventional pesticide plots (STELINSKI et al 2007). The total average number of insects captured per trap in the mating disruption plots, after installation of mating disruption, was compared with that obtained in conventional pesticide plots.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations